A cephalometric study of the skeletal and dento-alveolar effects of the modified Louisiana State University activator in Class II malocclusion. (11th July 2017) - Kang, Yunlong; Franchi, Lorenzo; Manton, David J; Schneider, Paul M
Summary: Objectives: To analyse the skeletal and dento-alveolar effects of the modified Louisiana State University activator (MLSUA) in Class II treatment. Materials and methods: A test group of 46 participants (25 females, 21 males) with Class II malocclusion treated with MLSUA followed by fixed appliances was compared with a matched Class II control group. Lateral cephalograms were taken at T1 (initial records), T2 (completion of MLSUA treatment), and T3 (before deband). The participants were also divided into two groups: pre-pubertal and pubertal according to skeletal maturity and three groups of different vertical facial patterns at the start of the treatment: brachyfacial, mesofacial, and dolichofacial. Statistical comparisons were performed with t -tests and analysis of variance (ANOVA). Results: Statistically significant supplementary mandibular growth (Co–Gn) in the test group (2.6 mm) was associated with improvement of overjet (OJ), overbite (OB), and molar relationship. Short-term mandibular growth was greater in pubertal than pre-pubertal groups (2.4 mm, P < 0.05). Mandibular incisors retroclined by 2.1 degrees after MLSUA treatment. The brachyfacial group showed greater reduction in the ANB angle and forward movement of pogonion. Mandibular, palatal, and occlusal plane angles showed insignificant change regardless of the facial type. Conclusions: MLSUA treatment corrected the Class II malocclusion by accelerating mandibular growth in the short-term with minimal dento-alveolar compensation, and the correction was maintained before deband. The treatment may be more effective if started at puberty. The mandibular, palatal, and occlusal planes remained stable throughout the treatment. Brachyfacial patients showed more favourable horizontal growth.